2007
DOI: 10.1038/sj.ejcn.1602702
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary pattern on the development of overweight in a Chinese population

Abstract: Objective: To examine dietary factors predisposing to overweight and obesity, taking into account age, gender, education level and physical activity. Design: Longitudinal population study. Setting: Community living subjects in Hong Kong. Subjects: One thousand and ten Chinese subjects participating in a territory wide dietary and cardiovascular risk factor prevalence survey in 1995-1996 were followed up for 5-9 years. Measurements: Body mass index (BMI) was measured. Information was collected on factors predis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 34 publications
2
76
1
Order By: Relevance
“…However, some trials have shown a beneficial association of the Mediterranean dietary pattern with weight loss (7), and the European Prospective Investigation into Cancer and Nutrition (EPIC)-Spain cohort confirmed a reduction in incident obesity associated with a higher adherence to the Mediterranean diet, although it was restricted only to overweight subjects (8). Another cohort did not find any association (9). In addition, a previous assessment in the Seguimiento Universidad de Navarra (University of Navarra Follow-Up Study) (SUN) cohort with only 2.3 y of follow-up showed no significant association between adherence to the Mediterranean diet and weight changes (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, some trials have shown a beneficial association of the Mediterranean dietary pattern with weight loss (7), and the European Prospective Investigation into Cancer and Nutrition (EPIC)-Spain cohort confirmed a reduction in incident obesity associated with a higher adherence to the Mediterranean diet, although it was restricted only to overweight subjects (8). Another cohort did not find any association (9). In addition, a previous assessment in the Seguimiento Universidad de Navarra (University of Navarra Follow-Up Study) (SUN) cohort with only 2.3 y of follow-up showed no significant association between adherence to the Mediterranean diet and weight changes (10).…”
Section: Introductionmentioning
confidence: 99%
“…In middle-aged participants in the Framingham Heart Study, soft drink consumption was found to be associated with higher prevalence and incidence of multiple metabolic risk factors [37]. Using a longitudinal study, Woo et al [38] found that increased snack consumption, which was mostly high in energy, was associated with increased risk of developing overweight in the Hong Kong Chinese population. In contrast, we observed that high factor scores with the high-energy food pattern were associated with much lower risk of a high TG/HDL-C ratio among women.…”
Section: Discussionmentioning
confidence: 97%
“…The DQI-I has also been used to evaluate the quality of diet in a Chinese population [32]. Four major aspects of the diet are assessed: variety, adequacy, moderation, and overall balance, each with subcomponents.…”
Section: Dietary Assessmentmentioning
confidence: 99%